Investigation of grain growth mechanisms in nanocrystalline Cu for Cu direct bonding - Shichen Xie; Ziting Ye; Zishan Xiong; Fuxin Du; Songpeng Zhao; K.N. Tu; Yuzheng Guo; Sheng Liu; Yingxia Liu (Journal of Materials Research and Technology)
Cu direct bonding technology is a critical approach for achieving highly integrated packaging structures. Recent studies demonstrate that utilizing nanostructured Cu enables a significant reduction in Cu–Cu bonding temperature, where nanoscale grain growth plays a crucial role. However, the thermodynamics and kinetics governing grain growth during the bonding process still lack comprehensive and precise theoretical elucidation. Therefore, in this study, the effects of grain structure, including grain size, grain orientation, and grain boundary type, on the grain growth kinetics were systematically investigated on electroplated nanocrystalline Cu films. The experimental results show that higher current density results in smaller grain size and faster growth rate, with the fastest case observed at 75 °C achieving grain coarsening from 100 nm to 2.5 μm within just 10 min. The quantitative kinetic analysis identifies that grain boundary energy and microstrain energy are the primary driving forces for grain growth as their magnitudes match the total driving force, while the dislocation energy is negligible because of a lower energy level. Notably, although the thermal strain energy also shows a low energy level, its preferential concentration at the film-substrate interface can drive a bottom-to-surface abnormal grain growth mode. Additionally, impurities are found to strongly hinder grain growth via the Zener pinning effect, acting as the primary resistance to the growth mechanism. This study reveals important details about the mechanisms and kinetics of grain growth in nanocrystalline Cu, which will serve as a useful reference for optimizing technical parameters in Cu–Cu direct bonding technology using nanocrystalline Cu.